Photo-oxidation of Pasteurized Milk in Polyethylene Pouch Packs - Nadeem, Muhammad; Anwar, Asif; Ullah, Rahman; Ahmad, Shakeel; Babar, Masroor Ellahi (Biological Sciences - PJSIR, 2017)
In the present study photo-oxidative stability of pasteurized milk packaged in polyethylene pouches was investigated. Milk packaged in three layer polyethylene pouch packs was exposed to 400, 600 and 800 l´ florescent light at 4 °C for 6 days, compared with a control (stored in dark). Light had a pronounced effect on fat content of milk with no effect on protein, lactose and ash content. Photo-oxidative stability of milk decreased as the intensity of light increased, peroxide value, anisidine value and conjugated dienes increased during the storage period of 6 days, higher values were observed in samples exposed to 800 l´ florescent light. After 6 days of storage period, milk exposed to 400 l´ florescent light did not reveal any oxidized flavour. The results of this study depicted that polyethylene pouches have the capability to resist photo-oxidation up to 400 l´ light.